Inactivation of swmA Results in the Loss of an Outer Cell Layer in a Swimming Synechococcus Strain - McCarren, J. (American Society for Microbiology, 2005)
The mechanism of nonflagellar swimming of marine unicellular cyanobacteria remains poorly understood. SwmA is an abundant cell surface-associated 130-kDa glycoprotein that is required for the generation of thrust in Synechococcus sp. strain WH8102. Ultrastructural comparisons of wild-type cells to a mutant strain in which the gene encoding SwmA has been insertionally inactivated reveal that the mutant lacks a layer external to the outer membrane. Cryofixation and freeze-substitution are required for the preservation of this external layer. Freeze fracturing and etching reveal that this additional layer is an S-layer. How the S-layer might function in motility remains elusive; however, this work describes an ultrastructural component required for this unique type of swimming. In addition, the work presented here describes the envelope structure of a model swimming cyanobacterium.